ExoMol molecular line lists – XLIII. Rovibronic transitions corresponding to the close-lying X 2Π and A 2Σ+ states of NaO. Issue 2 (12th February 2022) - Mitev, G B; Taylor, S; Tennyson, Jonathan; Yurchenko, S N; Buchachenko, A A; Stolyarov, A V
ABSTRACT: The sodium monoxide radical (NaO) is observed in night-glow in the Earth's mesosphere and likely has astronomical importance. This study concerns the optical transitions within the ground X 2 Π state and to the very low-lying ( T e ≈ 2000 cm −1 ) excited A 2 Σ + state. A line list consisting of rovibronic term values, allowed electric dipole transitions, Einstein coefficients, and partition functions for varying temperature are produced using a variational solution of the coupled-channel Schrödinger equations using the program duo . multi-reference configuration interaction (MRCI) ab initio calculations characterizing the potential energy curves of the two states, spin-orbit and L -uncoupling non-adiabatic matrix elements, as well as permanent and transition dipole moments were integral in the formation of the final deperturbation model. Ab initio potential energy curves are represented in the analytical Extended Morse Oscillator form and refined, along with the spin-orbit and L -uncoupling functions, by least-squares fitting to the available spectroscopic data. The input experimental data consisted of pure rotational transitions within the fine-structure components of the X 2 Π state for v ″ ∈ [0, 3] vibrational levels as well as the rovibronic A 2 Σ + ( v ′ = 0) ← X 2 Π( v ″ = 0) transitions, both with limited coverage over rotational excitation. The lack of data detailing the vibrational structure of the X and A states points to the need for further experimental study of higher excited levels, which would provide a more robust spectroscopic model. The NaO NaOUCMe line list is available via www.exomol.com and the CDS data base.